Diversity and the transition to adulthood in America - Ho, Phoebe, 1984-; Park, Hyunjoon; Kao, Grace (Sociology in the 21st century (University of California Press) ;, 2022)
"What does it mean to become an adult in the face of economic uncertainty and increasing racial and immigrant diversity? More than half of U.S. children are racial minorities and one in four are from immigrant families. Diversity and the Transition to Adulthood in America offers a comprehensive overview of young people across racial and immigrant groups and their paths through traditional markers of adulthood from finishing education, working full-time, and establishing residential independence to getting married and having children. The authors find that the transition to adulthood is increasingly fragmented, especially among those without college degrees"--